Ichthyosis bullosa of Siemens. Case report. - Tambe, S.A.; Jerajani, H.R.; Ghate, S.S. (European Journal of Pediatric Dermatology, 2011)
Ichthyosis bullosa of Siemens (IBS) is a dominant autosomal disease characterized by the absence of congenital erythroderma and by mild blistering explained by the superficial location of epidermolytic hyperkeratosis (granular and superficial prickly layers). In addition, IBS also has gray hyperkeratosis in elbows, knees, and other denuded areas with normal skin at the base (moulting or Mauserung phenomenon). We report an 11 month old baby girl presenting with IBS and showing excellent response to emollients.